San la Muerte : un métissage religieux insistant - Maureen Burnot (Journal de la Société des Américanistes)
This article proposes to trace the process of configuring the cult of San la Muerte in Argentina from archives, historical sources and ethnographic data. We begin by exploring the data that enable us to grasp how catholic and indigenous elements gradually combined at the time of the genesis of devotion, before questioning the transformation of the amulet from an object of power to a popular saint over the course of the 20th century. From a simultaneously anthropological and historical approach, we show that San la Muerte combines elements of Guarani and Christian traditions, and constitutes a mixed and autonomous expression of the Argentinian identity.